Durability simulation of elastomeric materials using finite element method (FEM) - Chieh, C. W.; Ali, Aidy; Sanuddin, Asmawi; Hosseinabadi, Reza Afshar (Universiti Putra Malaysia Press, 2010)
The paper presents a simulation work conducted on the elastomer subjected to cyclic loads. A 3D finite element model of elastomer specimen, in accordance to ASTM D412, was developed using CATIA and ANSYS commercial finite element (FEM) packages. Fatigue life predicted from the simulation was compared with well-documented published data and it showed an acceptable agreement. Meanwhile, the simulated strain-life results are slightly lower than the experimental data. Several factors which potentially influenced the variations of the results were noted. Finally, some recommendations are offered at the end of this study to further improve the simulation.